Social media addiction as a mediator of the associations between fear of COVID-19, mental health symptoms, and problematic alcohol use - Luk, Jeremy W.; Geda, Daniel W.; Stangl, Bethany L.; Cheng, Cecilia; Schwandt, Melanie L.; Goldman, David; Diazgranados, Nancy; Ramchandani, Vijay A. (Frontiers in Psychiatry, 2023)
Background Fear of COVID-19 is a risk factor for anxiety and depressive symptoms. During the COVID-19 pandemic, drinking to cope with psychological distress has been proposed as a key mechanism leading to problematic drinking. The goal of this study was to test social media addiction as a mediator linking fear of COVID-19 to mental health symptoms and problematic alcohol use. Methods In between April 6 and July 2 of 2022, 250 participants completed an online survey as part of the National Institute on Alcohol Abuse and Alcoholism COVID-19 Pandemic Impact on Alcohol Study. Path analyses were conducted to test the mediational pathways. Results Using the polythetic classification scheme, 13.2% (n = 33) of participants were classified as having social media addiction. Compared with participants without social media addiction, participants with social media addiction spent significantly more time on social media platforms and on digital communications with a family member or friend. They also reported greater fear of COVID-19, higher anxiety symptoms, and higher depressive symptoms. Path analyses indicated that social media addiction mediated the associations of fear of COVID-19 with anxiety and depressive symptoms. Furthermore, there were indirect pathways linking fear of COVID-19 to problematic alcohol use through higher social media addiction and higher anxiety and depressive symptoms. Conclusion Social media addiction may be a maladaptive coping mechanism that individuals with high fear of COVID-19 utilized to deal with uncertainty and perceived risks during the pandemic. Findings underscore the need to examine cognitions related to fear of COVID-19 and address excessive social media use in the context of mental health and alcohol interventions.